Simultaneous Determination of Four Active Ingredients in Sargentodoxa cuneata by HPLC Coupled with Evaporative Light Scattering Detection - Di-Hua Li; Yuan-Shan Lv; Jun-Hong Liu; Lei Yang; Yan Wang; Shu-Kun Zhang; Yu-Zhen Zhuo (International Journal of Analytical Chemistry)
A HPLC coupled with evaporative light scattering detection method had been developed for the simultaneous determination of 3,4-dihydroxyphenylethyl alcohol glycoside, salidroside, chlorogenic acid, and liriodendrin in the stem of Sargentodoxa cuneata. With a C18 column, the analysis was performed using acetonitrile and 0.2% formic acid aqueous solution as mobile phase in gradient program at a flow rate of 0.9 mL/min. The optimum drift tube temperature of evaporative light scattering detection was at 105°C with the air flow rate of 2.5 L/min. The calibration curves showed good linearity during the test ranges. This method was validated for limits of detection and quantification, precision, and reproducibility. The recoveries were within the range of 96.39%–104.64%. The relative standard deviations of intraday and interday precision were less than 2.90% and 3.30%, respectively. The developed method can be successfully used to quantify the four analytes in the stem of Sargentodoxa cuneata from various regions in China.